Different formation mechanisms of PAH during wood and coal combustion under different temperatures. (1st February 2020) - Han, Yong; Chen, Yingjun; Feng, Yanli; Song, Wenhuai; Cao, Fang; Zhang, Yanlin; Li, Qing; Yang, Xin; Chen, Jianmin
Abstract: Residential solid fuel combustion (RSFC) is a major contributor to polycyclic aromatic hydrocarbons (PAHs) in the atmosphere, which are strongly related to negative health impacts. During RSFC, the variations of PAH emission factors (EFs) and size-resolved profiles are known to be highly affected by fuel type and combustion temperature. In this study, to investigate the behavior of emitted PAH, combustion experiments were performed using three wood and three coal types under different temperatures (500 °C and 800 °C) in a quartz tube furnace. The results show that the average EFs of PAH (17-EPA-PAHs) from low temperature coal combustion were nearly three times higher than those from low temperature wood combustion. However, with high temperature, PAH emissions from wood combustion increased two-fold and that from coal combustion decreased by two orders. Furthermore, And the proportion of high-molecular-weight PAHs (HPAHs) increased with increasing temperature in wood combustion, but decreased in coal combustion. This indicates that PAH synthesis was the dominant process during wood combustion, while pyrolysis of coal supramolecular structure was the main formation pathway of PAH during coal combustion. In addition, more low-molecular-weight PAHs (LPAHs) were emitted, with 0.006 μm–0.050 μm and 0.223 μm–1 μm particles in the early burning stage, while more HPAHs were emitted in the later burning stage, with larger particles in the size range of 0.050 μm–0.223 μm. This means that the PAH formations were different during each burning stage. Graphical abstract: Image 1 Highlights: Quantification of PAHs in highly size resolved particles from 0.01 μm to 10 μm. PAHs from wood increase with temperature increasing while it is opposite from coal. PAHs emissions have different characteristics during each combustion processes. The formation pathway of PAHs during wood and coal combustions are different.